The Effect of Sustainability Report Disclosure and Sustainable Growth on Firm Value: The Moderating Role of CEO Power - Effendi, Dicky Rizky Ramadhan; Hendrawaty, Ernie; Febrianto, Igo (Amkop Management Accounting Review (AMAR), 2025)
Environmental issues have become a global concern, with the energy sector identified as the most significant contributor to greenhouse gas emissions. This study provides a novel contribution by examining the moderating role of CEO power, measured by CEO ownership, in strengthening the effects of sustainability reporting disclosure and sustainable growth on firm value. Focusing on Indonesia’s energy sector during the crisis and post-pandemic recovery period (2019–2023), the study employs a Random Effects GLS model with White two-way cluster robust standard errors. Firm value is measured using Tobin’s Q; sustainability disclosure is proxied by the Global Reporting Initiative (GRI) index; sustainable growth by the Sustainable Growth Rate (SGR); and CEO power by CEO ownership (CEOP). The results indicate that GRI has no significant impact on firm value, while SGR has a positive effect and CEOP has an adverse impact. However, the interaction terms GRICEOP and SGRCEOP exhibit significantly positive effects on firm value. These findings suggest that CEO ownership strengthens the relationship between corporate sustainability initiatives and firm value creation.